Antiphospholipidsyndrom - van Os, G. M. A.; Urbanus, R. T.; Agar, C.; Meijers, J. C. M.; de Groot, P. G. (Hämostaseologie, 2010)
The antiphospholipid syndrome (APS) is a non-inflammatory autoimmune disease characterized by the presence of antiphospholipid antibodies (aPL) in the plasma of patients with vascular thrombosis, recurrent complications of pregnancy, or both (1, 2). The presence of aPL in plasma of patients can be detected with either a prolongation of phospholipid dependent coagulation tests (lupus anticoagulant, LAC), or with solid phase immune assays against the protein β2-glycoprotein I (β2-GPI) or the phospholipid cardiolipin (anti-β2-GPI antibody ELISA and anti-cardiolipin antibody ELISA, respectively) (3). For a long time there was a lot of confusion on who had the syndrome and who not. To solve this dispute, an international consensus meeting was organized in Sapporo in 1999 to formulate classification criteria for patients with the antiphospholipid syndrome (4). These criteria have been updated in 2004 at another international consensus meeting in Sydney (5). The classification criteria were defined for scientific purposes and were aimed to be used as inclusion criteria in patient related studies. They were specifically not defined for diagnostic purposes. However, current practice is that these criteria are used as a diagnostic tool. This is very unfortunate because the specificity of the different aPL assays to detect the clinical manifestations that characterize APS are disputable. One of the aims of defining the criteria was to initiate studies to determine the value of the different anti-phospholipid antibody assays to serve as biomarker for the risk of thrombosis and pregnancy morbidity. The recent progress made on this important topic will be discussed.
Keywords: Antiphospholipid antibodies; Lupus anticoagulant; β2-glycoprotein I